The capital gain lock-in effect and long-horizon return reversal - Klein, Peter (Journal of Financial Economics, 2001)
This paper develops and tests an asset pricing model that allows for the presence of a capital gain lock-in effect. The principal empirical implication of this model is that stock returns exhibit reversal behavior over long horizons because of investors’ accrued capital gains. Empirical tests on the cross-section of stock returns find that long-horizon return reversal is primarily attributable to the effect of investors’ accrued capital gains and that the effect is nonlinear in the manner predicted by the model. These finds are robust to the addition of size and past total return to the empirical tests.